Estudo da audição de recém-nascidos de alto risco em maternidade de referência de Fortaleza - Ceará - Câmara, Marília Fontenele e Silva (1997)
This study reports on the prevalence of hearing loss among 600 lowbirthweigth infants born between January 1993 and December 1994 in major obstetric hospital (Maternidade Escola Assis Chateaubriand) in Fortaleza, Ceara, Brazil. Neonates were recruited soon after birth and followed up to the age of six month. The majority of infants’ mothers were young and had low level of education. About 7,2% of mothers had family history of hearing loss and 33,5% were first time pregnant. Thirteen percent of women did not attend antenatal consultations and 19,7% reported illnesses or complication during pregnancy including rubeola (2,2%). Most of newborns (73,3%) were premature and during the hospital stay, 60,0% were exposed to ototoxic drugs, 42,8% presented with hyperbilirubinemia, 26,3% had severe hypoxia and 1,2% were diagnosed bacterial meningitis. Screening and imitanciomatry tests were carried out in 403 children and 20 (5,0%) cases of sensorineural hearing loss and 18 (4,5%) cases of conductive hearing loss were identified.